Reflective primary teaching : meeting the Teachers' Standards throughout your professional career - Ewens, Tony; Cammack, Paul (Critical teaching (Critical Publishing), 2019)
Fully revised and updated, this text helps trainees and teachers develop their effectiveness by reflecting on, analysing and improving their practice in the light of a deeper understanding of the professional Teachers' Standards.